Analysis of C5 palsy in cervical myelopathy with massive anterior compression following laminoplasty - Chen, Guangdong (J Orthop Surg Res, 2018)
BACKGROUND: Little data is available about comparison of the incidence and clinical characteristics of the C5 palsy between patients of cervical myelopathy with occupying ratio greater than 50% and those with occupying ratio less than 50% following laminoplasty. METHODS: One-hundred eighteen patients with cervical myelopathy who underwent open door laminoplasty were reviewed in this study. The patients were divided into two groups: group A comprising 55 patients with an anterior occupying ratio greater than 50% and group B comprising 63 patients with an anterior occupying less than 50%. Clinical and radiological outcomes were assessed between two groups. RESULTS: No statistically difference was found in preoperative Japanese Orthopedic Association (JOA) score of both groups (10.7 ± 1.7 in group A vs 10.9 ± 1.1 in group B, P > 0.05). Improvements in postoperative JOA score were achieved, and there was a statistical difference (14.0 ± 1.4 in group A vs 14.8 ± 0.9 in group B, P < 0.05). Group A had a lower rate of recovery than group B (P < 0.05). Totally, 12 of 118 (10.2%) patients developed the C5 palsy postoperatively. C5 palsy occurred in 3 of 63 patients in the group B compared with 9 of 55 in the group A. Statistically significant difference was found in the incidence of C5 palsy between the two groups (P < 0.05). Furthermore, patients in group A required significantly longer recovery periods than group B. Both preoperative and postoperative MRI presented more levels of T2 high-signal lesion in group A than group B. The degree of posterior shift of the cord after posterior decompression in group A was less than group B (P < 0.05). CONCLUSIONS: Patients with a high degree of anterior compression have higher risk of C5 palsy than those with a relative low degree of anterior compression.